150 The Value of Early Biological Information in Glioblastoma Drug Development: A Health Economic Evaluation of Window-of-Opportunity Trials - Melyda Melyda; Sue Jowett; Peter Auguste; Victoria Wykes; Collin Watts; Gary Middleton; Vinton Cheng (Neuro-Oncology, 2026)
Abstract Introduction Window-of-opportunity (WoO) trials are increasingly proposed in glioblastoma drug development to test early biological activity (tumour penetration and target engagement), before progression to large, costly late-phase trials. While WoO designs may improve early decision-making, they introduce additional operational complexity and upfront costs. Their economic value remains uncertain. Methods An early decision-analytic model was developed to assess the cost-effectiveness of incorporating a WoO stage into the development pathway of hypothetical glioblastoma immunotherapy. Three strategies were compared: conventional development without WoO, early WoO (pre-/peri–Phase I), and intermediate WoO (post–Phase I/Phase II run-in). The model followed the Phase I–III sequence, incorporating glioblastoma-specific attrition adjustments and odds-based uplifts after a positive WoO signal. Phase-specific costs were derived from published estimates and inflated to 2025 GBP (£). From research and development perspective, the model estimated total development costs and the expected number of candidates reaching Phase III success. Deterministic and probabilistic sensitivity analyses were conducted. Results Preliminary results suggest that incorporating a WoO stage may reduce total development costs and increasing the expected number of candidates reaching Phase III success compared with the conventional pathway. Using the conventional strategy as a benchmark (£22.97M), early WoO generated greater net economic value (£17.16M) than intermediate WoO (£5.44M). Probabilistic sensitivity analysis shows most simulations remaining economically favourable relative to this benchmark. Results were most sensitive to parameters determining the probability of detecting biologically meaningful signal and the extent to which that signal influenced downstream decisions. Conclusion Incorporating WoO into the clinical development pathway for glioblastoma immunotherapies could improve cost-effectiveness of drug development by reducing costs and prioritising candidates with clearer biological activity. Further work is needed to refine key inputs and identify optimal WoO designs.